THE EFFECT OF EMOTIONAL INTELLIGENCE TOWARDS STUDENTS' MATHEMATICS PROBLEM SOLVING ABILITY: A META-ANALYSIS CORRELATIONAL STUDY - Noor Annisah Sholehah; Dadang Juandi; Surya Kurniawan (Universitas Lambung Mangkurat, 2022)
The literature has shown that emotional intelligence can control a person's rational decision-making and also contribute to mathematical problem-solving. There have been many correlational studies investigating the effect of emotional intelligence on the mathematical problem-solving abilities of students in Indonesia. This study aims to summarize the effect size values given by the primary study through meta-analysis techniques. Twenty-one primary studies that have been published by journal publishers, theses, and proceedings in the last ten years and meet the inclusion criteria will be analyzed. Data analysis using Jeffreys's Amazing Statistics Program (JASP) software with the stages of investigating publication bias, random or fixed effect models, and statistical hypothesis testing. Based on the random effects model, the results showed that there was a positive effect of emotional intelligence on students' mathematical problem-solving abilities in Indonesia with the category of medium positive effect (r = 0.6; p < 0.01). These results suggest for students and learners to give serious attention to students' emotional intelligence to improve their mathematical problem-solving abilities. Keywords: Emotional Intelligence, Emotional Quotient, Mathematics Problem Solving, Meta-Analysis.